Parent Responsibility Towards Criminal Actions Of Traffic Accident By Children Which Sustained Others Death - Himawan Aji Angga; Ira Alia Maerani (Law Development Journal, 2020)
The aim of this studyto find out and analyze the efforts made by parents and Polrestabes Semarang in overcoming traffic accidents by children that cause other people to die, the resulting losses, as well as the form of parental responsibility for traffic accidents by children in the jurisdiction Polrestabes Semarang. The research problem is analyzed by the theory of the operation of law in society, the theory of criminal liability and the theory of substitute liability. The approach method used is juridical sosilogical method, the specification in this research is descriptive data analysis used is qualitative. The results of the study: That the factors that cause the use of motorized vehicles by children in the jurisdiction of the Semarang Police are ignorance, personal encouragement, family encouragement, social encouragement, disinterest and opinions are not obliged to order traffic. That in order to overcome this problem, it has been done Efforts by the Traffic Police of the Semarang Police, include Pre-emptive, preventive and repressive efforts. Parents must also try to encourage the school to prepare school pick-up facilities, issue restrictions on using motorbikes, and not provide parking spaces. Parents can also make efforts by encouraging the Semarang City Government to provide transportation.